Trance-like episodes interpreted as rasuk: a case managed in a shariah-compliant tertiary hospital - Hassan, Muhammad Afiq; Ismail, Mohd Helmie; Saiful Suhardi, Mohd Iman (Medicine & Health Journal, 2025)
Introduction: Spirit possession, locally known as rasuk in Malay culture, is traditionally perceived as an altered state of consciousness attributed to supernatural influence. Its manifestations often overlap with medical or psychiatric conditions, complicating diagnosis and management. Many affected individuals initially pursue religious healing or ruqyah (spiritual recitation) before seeking hospital care. We present a case of alleged spirit possession admitted to a Shariah-compliant tertiary hospital, highlighting the collaborative role of the spiritual care team in supporting clinical management within an integrative healthcare setting. Case Description: An 18-year-old woman presented with behavioral changes, lethargy, irrelevant speech, child-like behavior, and auditory experiences for two days. She reported feeling watched and claimed to have bruises, though none were observed. Previous episodes had resolved with ruqyah. On admission, systemic and neurological examinations were normal, while blood tests, urine toxicology, and CT brain excluded structural, metabolic, or toxic causes. The psychiatry team diagnosed acute stress reaction, while medical teams investigated for encephalitis and autoimmune conditions. After a session of ruqyah, the patient regained calmness and full consciousness. She declined lumbar puncture and was discharged against medical advice. Discussion: This case illustrates the diagnostic complexity when symptoms overlap between psychiatric, neurological, and culturally influenced presentations. While psychiatric assessment suggested an acute stress reaction, concurrent exclusion of organic causes such as encephalitis was crucial. The patient’s rapid improvement following spiritual recitation emphasises the importance of culturally sensitive spiritual care. Collaboration between medical, psychiatric, and spiritual care teams can optimise patient outcomes in contexts where cultural beliefs strongly shape health-seeking behavior. Conclusion: This case highlights the importance of integrated, culturally informed care in managing possession-like states. A Shariah-compliant hospital framework enabled holistic management, combining medical, psychiatric, and spiritual approaches to enhance engagement, reduce stigma, and improve recovery.